The Influence of Teacher Competence and Academic Supervision by Principals on Teacher Performance - Priyasmimana, Priyasmimana; Habib, BAWA Ibn; Haenilah, Een Yayah (PPSDP International Journal of Education, 2022)
The purpose of this study is to explain and assess if teacher competency and principal academic supervision effect teacher performance at High School PGRI 2 Palembang. This study employed a quantitative methodology. This study's demographic and sample consisted of 64 teachers of High School PGRI 2 Palembang. Data collection methods such as surveys and document studies. The survey results demonstrate that teacher competency and academic supervision from the principal have a substantial influence on teacher performance at High School PGRI 2 Palembang, both separately and together. This study is still in its early stages since it looks at teacher competency and academic supervision as it relates to teacher performance, particularly at the high school level. It is believed that this research would help schools, particularly school administrators, enhance teacher performance by boosting competency and executing appropriate academic supervision.